2019
DOI: 10.3389/fendo.2019.00594
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulin Glargine and Human Insulin in the Regulation of Thyroid Proliferation Through Mitogenic Signaling

Abstract: Our aim was to investigate whether human insulin (HI) or insulin glargine treatment could promote the proliferation of thyroid cells and determine the association between type 2 diabetes and thyroid disease. Rats were treated with different doses of HI and insulin glargine. Plasma glucose and the phosphorylation levels of the insulin receptor (IR), insulin-like growth factor 1 receptor (IGF-1R), protein kinase B (Akt), and extracellular signal-regulated kinase 1/2 (ERK1/2) were measured. A total of 105 rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous clinical study has found that women with T2DM treated with long-term subcutaneous insulin injection have an increased incidence of breast cancer (28). Sheng et al found that both human insulin and glargine did stimulate thyroid cell proliferation at high doses (29). From the evidence mentioned above, it is reasonable to speculate that hyperinsulinemia (both endogenous and exogenous insulin) may play a role in cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical study has found that women with T2DM treated with long-term subcutaneous insulin injection have an increased incidence of breast cancer (28). Sheng et al found that both human insulin and glargine did stimulate thyroid cell proliferation at high doses (29). From the evidence mentioned above, it is reasonable to speculate that hyperinsulinemia (both endogenous and exogenous insulin) may play a role in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al. found that both human insulin and glargine did stimulate thyroid cell proliferation at high doses ( 29 ). From the evidence mentioned above, it is reasonable to speculate that hyperinsulinemia (both endogenous and exogenous insulin) may play a role in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin glargine stimulated phosphorylation of both IR and IGF-1R, in contrast to detemir, which only induced phosphorylation of IR but not IGF-1R in colorectal cells. Based on in vivo data, therapeutic doses of glargine do not cause thyroid cell proliferation [142]. Detemir had much lower capacity to stimulate AKT phosphorylation in comparison to glargine [141].…”
Section: Insulinmentioning
confidence: 99%
“…[104] In vitro Metformin FTC-133 (human FTC cell line), K1E7 (subclone of K1 cell line from human PTC), RO82-W-1 (human FTC cell line), 8305C (human ATC cell line), TT (human MTC cell line), Nthy-ori 3-1 (human normal thyroid follicular cells) -Inhibition of cell proliferation, colony formation, and cell migration -No effect on DNA repair -induction of cell cycle arrest and apoptosis ± mice (spontaneously develops metastatic FTC; animals harbor a mutated thyroid hormone receptor-β and haploinsufficiency of Pten) HFD vs. low fat diet (LFD): -Stimulation of thyroid tumor growth -Increase in Ki-67 positive cells and protein abundance of p-Rb and cyclin D1 -No difference in activation of MAPK and PI3K signaling pathways -Promotion of anaplastic change in thyroid cancers -Increased expression of Mcl1, Bcl2l1, Ccnd1, and Vegfa (STAT3 target genes) and activation of leptin-JAK2-STAT3 signaling as one pathway that mediates obesity-induced aggressive tumor progression. [167]In vivoInsulin: HI and GI Female Wistar rats -Dose-dependent effect on Akt and ERK1/2 phosphorylation, GI > HI -Higher and longer Akt and ERK1/2 phosphorylation after GI vs. HI -Dose-dependent increase in Ki-67 positive cells(HI vs. GI at highest doses) -High doses of HI primarily affect IR phosphorylation -High doses of GI primarily affect IGF-1R phosphorylation[142]…”
mentioning
confidence: 99%